CoSa Management System 2.0 / Ling-Ling Ung, Mohd Muizzuddin Arif Moni and Emmanuel Shanmuganathan - Ling-Ling, Ung; Moni, Mohd Muizzuddin Arif; Shanmuganathan, Emmanuel (Universiti Teknologi MARA, Negeri Sembilan, 2023)
The CoSA Management System represents an innovative technical solution that significantly transforms member involvement within the College of Computing, Informatics and Mathematics (KPPIM) at the UiTM Sabah Branch. The system aims to automate the member registration process and establish a consolidated platform for efficient information transmission, thereby serving as a catalyst for boosting the faculty experience. The primary objective of the CoSA Management System is to optimize the complex procedures involved in member registration. The system's implementation greatly enhances the registration process's efficiency by transitioning from manual procedures to a user-friendly digital platform. This transition eliminates the need for laborious paperwork and reduces the time spent waiting for registration. The innovation has a broader reach, as its aim is to cultivate a cohesive community within the KPPIM by providing a centralized platform for members to obtain up-to-date information on events, programs, workshops, and news. Implementing a centralized strategy enhances communication and fosters a sense of togetherness among the members. The system's efficacy relies on its comprehensive features, which effectively meet the diverse needs of KPPIM members. The platform enables streamlined registration for various events, seminars, workshops, and other activities, utilizing technology to ease a previously intricate procedure. Furthermore, individuals are granted the authority to independently oversee their registrations, encompassing tasks such as modifying personal information and terminating their involvement, all inside the user-friendly interface. The empowerment described aligns with the underlying principles of CoSA, as it aims to provide a customized experience for every individual involved. The CoSA Management System is designed and developed based on the System Development Life Cycle (SDLC). This technique guarantees a methodical approach throughout the entire process, from the initial idea to the final implementation, ensuring the system's dependability, scalability, and long-term viability. The advantages derived from the CoSA Management System are significant. The system enhances administrative operations by implementing automation and centralizing member registration, saving time and resources for the institution and its constituents. The system ultimately transforms the dynamics of member engagement, promoting effectiveness, communication, and community development inside the KPPIM at UiTM Sabah Branch.